Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the zeros of the quadratic equation [tex]\( y = x^2 - 6x - 4 \)[/tex] by completing the square, we will transform the equation into a form that makes it easier to solve. Here are the detailed steps:
1. Start with the given equation:
[tex]\[ y = x^2 - 6x - 4 \][/tex]
2. Set [tex]\( y \)[/tex] to 0 to find the zeros:
[tex]\[ 0 = x^2 - 6x - 4 \][/tex]
3. Move the constant term to the right side:
[tex]\[ x^2 - 6x = 4 \][/tex]
4. Complete the square on the left side. To do this, take half of the coefficient of [tex]\( x \)[/tex], square it, and add it to both sides of the equation. The coefficient of [tex]\( x \)[/tex] is [tex]\(-6\)[/tex], half of [tex]\(-6\)[/tex] is [tex]\(-3\)[/tex], and squaring [tex]\(-3\)[/tex] gives [tex]\(9\)[/tex]:
[tex]\[ x^2 - 6x + 9 = 4 + 9 \][/tex]
[tex]\[ (x - 3)^2 = 13 \][/tex]
5. Take the square root of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x - 3 = \pm \sqrt{13} \][/tex]
6. Solve for [tex]\( x \)[/tex] by isolating it:
[tex]\[ x = 3 \pm \sqrt{13} \][/tex]
The zeros of the quadratic equation [tex]\( y = x^2 - 6x - 4 \)[/tex] are:
[tex]\[ x = 3 - \sqrt{13} \][/tex]
[tex]\[ x = 3 + \sqrt{13} \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{C. \; x = 3 \pm \sqrt{13}} \][/tex]
1. Start with the given equation:
[tex]\[ y = x^2 - 6x - 4 \][/tex]
2. Set [tex]\( y \)[/tex] to 0 to find the zeros:
[tex]\[ 0 = x^2 - 6x - 4 \][/tex]
3. Move the constant term to the right side:
[tex]\[ x^2 - 6x = 4 \][/tex]
4. Complete the square on the left side. To do this, take half of the coefficient of [tex]\( x \)[/tex], square it, and add it to both sides of the equation. The coefficient of [tex]\( x \)[/tex] is [tex]\(-6\)[/tex], half of [tex]\(-6\)[/tex] is [tex]\(-3\)[/tex], and squaring [tex]\(-3\)[/tex] gives [tex]\(9\)[/tex]:
[tex]\[ x^2 - 6x + 9 = 4 + 9 \][/tex]
[tex]\[ (x - 3)^2 = 13 \][/tex]
5. Take the square root of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x - 3 = \pm \sqrt{13} \][/tex]
6. Solve for [tex]\( x \)[/tex] by isolating it:
[tex]\[ x = 3 \pm \sqrt{13} \][/tex]
The zeros of the quadratic equation [tex]\( y = x^2 - 6x - 4 \)[/tex] are:
[tex]\[ x = 3 - \sqrt{13} \][/tex]
[tex]\[ x = 3 + \sqrt{13} \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{C. \; x = 3 \pm \sqrt{13}} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.